Cenicriviroc inhibits trans-endothelial passage of monocytes and is associated with impaired E-selectin expression. Issue 6 (8th August 2018) - D'Antoni, Michelle L; Mitchell, Brooks I; McCurdy, Sara; Byron, Mary Margaret; Ogata-Arakaki, Debra; Chow, Dominic; Mehta, Nehal N; Boisvert, William A; Lefebvre, Eric; Shikuma, Cecilia M; Ndhlovu, Lishomwa C; Baumer, Yvonne
Abstract: Incidences of cardiovascular diseases (CVD) are high among virologically suppressed HIV-infected individuals. Monocyte activation and trafficking are key mechanisms in the evolution of CVD. We studied the ability of cenicriviroc (CVC), a dual C-C chemokine receptor type 2 (CCR2) and CCR5 antagonist, to influence the migration of monocytes from HIV-infected individuals on antiretroviral therapy (ART). Monocytes were derived from 23 ART-suppressed HIV-infected and 16 HIV-uninfected donors. In a trans-endothelial migration model, monocytes, and human aortic endothelial cells (HAoECs) were exposed to cenicriviroc and migrated monocytes, quantified. Expression of CCR2 and CCR5 on monocytes and adhesion molecules (E-selectin, ICAM-1, VCAM-1, PECAM-1, and CD99) on HAoECs were measured. The single antagonists, BMS-22 (CCR2), and maraviroc (CCR5), served as controls. When both HAoECs and monocytes together were exposed to the antagonists, cenicriviroc led to a greater decrease in monocyte migration compared to BMS-22 or vehicle in both HIV-infected and HIV-uninfected groups ( P < 0.05), with maraviroc having no inhibitory effect. Cenicriviroc treatment of HAoECs alone decreased monocyte migration in the HIV-infected group when compared to vehicle ( P < 0.01). Inhibition of migration was not evident when monocytes alone were exposed to cenicriviroc, BMS-22 or maraviroc. Incubation of HAoECs with cenicriviroc decreased E-selectin expression ( P = 0.045) but had limited effects on the other adhesion molecules. Cenicriviroc inhibits monocyte trans-endothelial migration more effectively than single chemokine receptor blockade, which may be mediated via disruption of monocyte-endothelial tethering through reduced E-selectin expression. Cenicriviroc should be considered as a therapeutic intervention to reduce detrimental monocyte trafficking. Cenicriviroc, a dual CCR2 and CCR5 antagonist, inhibits monocyte trafficking in an in vitro trans-endothelial migration assay more effectively than a single chemokine receptor blockade.